Salts of the Weakly Coordinating Anion [Al(OTeF5)4]– containing Reactive Counterions. Issue 21 (12th July 2018) - Hoffmann, Kurt F.; Wiesner, Anja; Subat, Noah; Steinhauer, Simon; Riedel, Sebastian
Abstract : Six different salts of the weakly coordinating anion [Al(OTeF5 )4 ] – were synthesized and characterized spectroscopically. The alkali and silver salts M [Al(OTeF5 )4 ] ( M = Ag, Li, Na, K, Rb) were obtained by a protonation reaction involving the Brønsted acid H[Al(OTeF5 )4 ](solv) . In the case of the lithium and silver salt, crystals of the solvent‐coordinated [Li(thf)4 ][Al(OTeF5 )4 (thf)2 ] and [Ag(thf)6 ][Al(OTeF5 )4 (thf)2 ] were characterized by low‐temperature X‐ray diffraction, revealing a sixfold coordinated central aluminum atom. By a metathesis reaction, the oxidizing nitrosonium salt [NO][Al(OTeF5 )4 ] was obtained and its reactivity was demonstrated by a reaction with white phosphorus. By low‐temperature NMR spectroscopy the selective formation of [NOP4 ] + species was confirmed. All of the prepared salts represent useful starting materials for the further introduction of the weakly coordinating anion [Al(OTeF5 )4 ] – into a given system. Abstract :